2010
DOI: 10.1021/ma1007013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Methionine- and Cysteine-Substituted Phosphazenes

Abstract: The preparation of phosphazenes that possess reversible cross-linking groups to control mechanical stability and hydrolysis has been accomplished using cysteine and methionine amino acid side groups. Small molecule models and linear polymeric phosphazenes that contain methionine ethyl ester and cysteine ethyl disulfide ethyl ester side groups were synthesized. Protection of the free thiol groups was carried out to circumvent unwanted cross-linking of the phosphazenes through the cysteine ethyl ester N- and S-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…fluorescence intensity was higher than 25,000. This confirmed that the solubility of NR in water was not affected by pH, in agreement with the previous report 42. This time-dependent release behaviour strongly supports that the drug release was indeed 100 resulted from cleavage of disulfide bonds, rather than the effect from diffusion, osmotic pressure, or even improved solubility under different pH values, etc.…”
supporting
confidence: 92%
“…fluorescence intensity was higher than 25,000. This confirmed that the solubility of NR in water was not affected by pH, in agreement with the previous report 42. This time-dependent release behaviour strongly supports that the drug release was indeed 100 resulted from cleavage of disulfide bonds, rather than the effect from diffusion, osmotic pressure, or even improved solubility under different pH values, etc.…”
supporting
confidence: 92%
“…The success of these secondary transformations often depends on the main chain being protected by bulky substituents so that access by the reagent to the phosphorus and nitrogen skeletal atoms is restricted or prevented. This technique has been used extensively in our program to prepare biomedical polymers and other specialized derivatives with specific functionality . A few examples are shown in Figs and . Block copolymer formation via the living cationic polymerization .…”
Section: Polyphosphazenes With Two or More Different Side Groupsmentioning
confidence: 99%
“…57 The synthesis of cysteine-and methioninefunctionalized polyphosphazenes has also been reported. 58 Moreover, peptidemodified polyphosphazenes when blended with polyesters can undergo hydrolysis to yield porous microstructures which are robust and non-toxic matrices for the regeneration of tissues. 59 Films consisting of alternating layers of poly[bis(methoxyethoxy)phosphazene] and polyacrylic acid (PAA) were synthesized and shown to display ionic conductivities that were an order of magnitude better than previous hydrogen-bonded polymer films.…”
Section: Polyphosphazenes and Related Polymersmentioning
confidence: 99%